Design of Management Information Systems Memorandum of Understanding (MoU) And Memorandum of Agreement (MoA) Universitas Darussalam Gontor - Oddy Virgantara Putra; Yoke Suryadarma; Muhammad Arsyad Maulana (Unusa Press, 2021)
The Memorandum of Understanding (MoU) at Universitas Darussalam Gontor (UNIDA) is an important activity that can be proven by the number of MoUs that have been carried out. However, because the management of the MoU is still manual, there is a risk of damage, loss, and duplication of the MoU data. In this research, an information system for the Bureau of Cooperation, Alumni, and International Affairs UNIDA has been built to meet the bureau's needs in managing data correctly so that students and lecturers can utilize the data. The system is made in the form of a website using the concept of Model-View-Controller (MVC) and Single Page Application (SPA) by applying the SDLC (System Development Life Cycle) methodology. The study results show the satisfaction value of the respondent's assessment is at 4.11 on a scale of five, which means that this information system provides satisfaction to users. In the subsequent project research, this system can develop an authentication site for user security.